Improving Business Performance of Getuk Nyimut SMEs in Kudus Regency by Marketing, Capital, Production Technology and Product Diversification - Marka, Mira Meilia (Universitas Islam Negeri Sunan Kudus, 2021)
This research used qualitative research method with phenomenological approach. The object of this research was SMEs of getuk nyimut in Kudus Regency. The increasing number of getuk nyimut’s SMEs along the area towards Muria Mountain tourism has made it difficult for SMEs to survive in the market. SMEs which are sold with simple sales locations and maintain original products have not been able to increase sales significantly. This research aimed to analyse the effect of marketing, capital, production technology and product diversification on the competitive advantage of getuk nyimut SMEs in Kudus Regency. The results of the research were obtained from 14 informants consisting of entrepreneurs of getuk nyimut, academics and local governments. The results showed SMEs of getuk nyimut have problems in some aspects such as marketing, capital, production technology and product diversification. To overcome the problems faced by participation from some parties, not only from entrepreneurs but also getuk community and local governments. The result of this research showed that marketing, capital, production technology, product diversification which are well managed can increase competitive advantage of SMEs in Kudus Regency especially getuk nyimut’s entrepreneurs.